THE EFFECT OF COMPENSATION AND LEADERSHIP STYLE TOWARDS EMPLOYEES PERFORMANCE - Fitrianingrum, Dyka Febriana (Manajemen Bisnis, 2019)
This study aims to describe the compensation, leadership style, and the performance of employees and also to know the influence of compensation and leadership style partially and simultaneously to the performance of employees of PT. Hartria Akas Green Sejahtera. The respondents of this research were all employees of drivers and conductors of Patas Bus consisting of 75 people. The sampling technique used was census method. In analyzing the data, the researcher used multiple scale and linier regression. The hypothesis testing used t-test and F-test. The result of scale range analysis showed that the performance of the employees is high, the compensation is good, and the leadership style applied by company is achievement oriented. In addition, the results of multiple linier regression analysis portrayed that the compensation and leadership style influence significantly, partially and simultaneously to the performance of employees of PT. Hartria Akas Green Sejahtera.